Subdiaphragmatic Presentation of Hodgkinâs Lymphoma with Peripheral Neuropathy - Parvin, Rukhsana; Chowdhury, Fazle Rabbi; Shams, Md Ziaus; Bari, Md Shafiqul; Alam, Md Billal (Journal of Medicine, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> A 27 years old, unmarried male day labour, hailing from Jhalkathi presented to us with the complains of anorexia, weight loss and gradual weakness of all limbs for 6 months. On examination, he had features of peripheral neuropathy, but other systemic examinations were unremarkable. He did not have any significant lymphadenopathy or hepatosplenomegaly.He was diagnosed as a case of Hodgkin's Lymphoma, lymphocyte predominance, after diagnostic laparotomy followed by excisional biopsy from intraabdominal lymph node.Subdiaphramatic Hodgkin's lymphoma is rarely occurs and may present in several ways. Peripheral neuropathy is one of these. We treated him with Doxorubicin, Bleomycin, Vinblastin and Dacarbazine with successful outcome. Â DOI = 10.3329/jom.v9i1.1429 Â Â J MEDICINE 2008; 9 : 62-63